Responsibilities of Regional Heads in Fulfilling Disability Rights - Tindo’o, Mirnawati (CV. Rayyan Dwi Bharata, 2024)
Persons with disabilities are people who have experienced physical, intellectual, mental or sensory limitations for a long time and may have difficulty interacting with their environment and participating fully and effectively with other citizens. Law Number 8 of 2016 concerning Persons with Disabilities requires the government and society to provide guidance on efforts to improve the social welfare of persons with disabilities. The aim is to protect and realize the rights of persons with disabilities to carry out respect, promotion, protection and fulfillment of rights to fully respect human rights and basic freedoms for persons with disabilities and the like. The method used is a juridical method which is a concept from the results of the treatment of Law 8 /2016 as part of the work Adapting the principles of the Convention on the Rights of Persons with Disabilities (CRPD) in positive law and government bureaucracy in Indonesia.